DETERMINANTS OF YOUTH PARTICIPATION IN FOOD CROPS PRODUCTION IN SONG LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA - Panny Mascot YUNUSA; Dengle Yuniyus GIROH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study examined the Determinants of Youth Participation in Food Crops Production in Song Local Government Area of Adamawa State, Nigeria. The specific objectives were to describe the socio-economic characteristics of the youth, examine the determinants of youth participation in food crops production and identify constraints faced by the respondents. Data were collected with the aid of a structured questionnaire administered to 121 randomly selected respondents. Analytical tools used in the analysis of data were descriptive statistics and logit regression. Results showed that 55.38 %, of the respondents were in the range of 18 – 29 years with mean age of 27 years, 58.68% were married with the mean household size of 3 people respectively. Also, 95.87 % were literate and attained one form of formal education or the other with mean annual income of N185,911. Furthermore, 87.60% participated in food crops production, 71.69 % of the respondents had 1 to 5 years of experience with mean farming experience of 7 years, 75.47 % cultivated less 3.44 hectares of farm land with an average farm size of 2.5 ha. Logit regression result revealed that 82.27 % of the variations in the participation of youths were explained by the variables in the model. Marital status, farm size, income and education were the major determinants of youth participation in food crops production. Inadequate capital, poor government attention on agricultural sector, poor roads and rural infrastructure and inadequacy of inputs at the right time were the major constraints to youth participation in food crops production. Agricultural sector be given priority attention by government, re-introduction of subsidy on inputs and formation of viable cooperative groups to facilitate access to farm credit were recommended in the paper.